2008
DOI: 10.1002/jcp.21528
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mitochondrial transcription factor A (TFAM) during porcine gametogenesis and preimplantation embryo development

Abstract: Mitochondrial transcription factor A (TFAM) is responsible for stability, maintenance, and transcriptional control of mitochondrial DNA (mtDNA). We have studied the expression and distribution of TFAM in the gametes and preimplantation embryos of the domestic pig (Sus scrofa). We hypothesized that TFAM is not present in the boar sperm mitochondria to reduce the possibility of paternal mtDNA propagation in the progeny. In contrast, we anticipated that Tfam gene is expressed in a developmental stage-dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 116 publications
2
17
0
3
Order By: Relevance
“…The presence of a high molecular weight band, instead of ~25KD band, suggests that high glucose polyubiquinated TFAM. In support others have shown tetra-ubiquitination of TFAM in sperm extracts during porcine gametogenesis (Antelman, Manandhar et al 2008). Figure 4b presents the quantification of the ubiquitinated TFAM.…”
Section: Resultssupporting
confidence: 82%
“…The presence of a high molecular weight band, instead of ~25KD band, suggests that high glucose polyubiquinated TFAM. In support others have shown tetra-ubiquitination of TFAM in sperm extracts during porcine gametogenesis (Antelman, Manandhar et al 2008). Figure 4b presents the quantification of the ubiquitinated TFAM.…”
Section: Resultssupporting
confidence: 82%
“…S12). Mitochondrial membrane and matrix proteins such as prohibitin and TFAM, as well as those identified in the present study by copurification with the UBA domain of SQSTM1 are ubiquitinated (14,15). Thus, it is possible that the whole sperm mitochondrial sheath is recognized by the oocyte autophagy machinery as one large aggresome.…”
Section: Discussionmentioning
confidence: 78%
“…Previous data that have suggested that TFAM might be a limiting factor in mtDNA replication in mammalian oocytes and embryos. In the pig, although Tfam declines during oocyte maturation (Spikings et al 2007), both TFAM (Antelman et al 2008) and mtDNA (Spikings et al 2007) accumulate during this time. Additionally, as discussed earlier, mtDNA replication resumes in embryos near the time of implantation (Piko & Taylor 1987, Ebert et al 1988, Kameyama et al 2007, May-Panloup et al 2007; in mouse and cow, this is correlated with a sharp increase in the quantity of Tfam , May-Panloup et al 2007.…”
Section: Discussionmentioning
confidence: 99%